HISTOLOGICAL OF CHANGES IN THE AMNIOTIC MEMBRANE AND PLACENTAL VILLOUS BASAL LAMINA IN COMPLICATED PREGNANCIES - Yusuf NERGIZ (Rojan GÜMÜŞ, 2019)
Aim: This study aimed to histological changes compare placental villous basal lamina and amniotic membrane changes in complicated pregnancy. Methods: Studies were performed on the human placentas, delivered between 24-39 weeks of gestation. Patients were separated equally into 4 groups (Control, preeclampsia (PE), gestastional diabetes (GD), and HELLP syndrome groups) Placental tissue samples were dissected and fixed in 10% neutral formalin buffer. Routine paraffin tissue protocol was followed. Some of sections were stained with Periodic Acid Schiff. Remaining sections were stained with integrin alpha-6 antibody.To define expression percentage, mean of the staining area/total staining area ratio were calculated. The statistical significance of the expression percentages was compared by One Way ANOVA and Tukey tests with SPSS Statistics V24 software. Results: In PAS-stained preeclamptic, HELLP and gestational diabetes groups placental villous basal lamina and vasculo-syncytial membranes were thicker than the control group. A significant difference was observed in all 3 groups compared to the control group the placental villous basal lamina thickness of the HELLP group was found to be significantly different from all three groups. In chorionic villi of HELLP group, dense integrin expression was found in placental villous basal lamina similar to that in GD and preeclampsia groups. The HELLP group was significantly different from all groups. Conclusion: In preeclampsia, gestational diabetes and HELLP placentas, placental viiöz basal lamina and amniotic membrane significantly thickened and structural changes were observed.